AMPLIFIED FRAGMENT LENGTH POLYMORPHISM (AFLP) ANALYSIS OF GENETIC DIFFERENTIATION AMONG ASCOCHYTA BLIGHT RESISTANT ACCESSIONS OF FABA BEAN - Uyek Malik Yakop (Department of Agronomy Faculty of Agriculture University of Mataram and Indonesian Society of Agronomy Branch NTB, 2008)
ABSTRACT Ascochyta blight caused by Ascochyta fabae is one of the most destructive diseases on faba bean. There was variation among putatively resistant faba bean accessions in their response to various isolates of A. fabae. The present study was conducted to investigate genetic similarities among the Ascochyta blight resistant faba bean accessions and to identify whether there was a relationship between the genetic similarity and genetic control of resistance to A. fabae, as well as between the genetic similarity and origin of the accessions. Amplified Fragment Length Polymorphism (AFLP) analysis was utilised to identify the genetic distance among 20 resistant and 2 susceptible accessions. Three primer combinations (PstACA-MseCAG, PstACA-MseCCA and Ps ACA-MseCGA) revealed a high level of polymorphisms. The average genetic distance over all accessions was 0.34 with the pair-wise ranged from 0.09 to 0.53. The phylogenetic tree divided the 22 accessions into two major groups and several groups of two and three. The analysis was inconclusive when the genetic control of resistance to A. fabae, the region of origin and the source population were compared to the genetic distances among the accessions. ABSTRAK Bercak daun yang disebabkan oleh Ascochyta fabae merupakan salah satu kerusakan karena penyakit yang parah terhadap kacang babi (faba bean). Terdapat perbedaan respon diantara galur-galur yang tahan terhadap isolate A. fabae yang berbeda. Penelitian ini telah dilakukan dengan tujuan untuk mengkaji keeratan genetic diantara galur-galur kacang babi yang tahan terhadap isolate A. fabae dan untuk melihat apakah ada hubungan antara keeratan genetic dengan gen pengontrol ketahanan terhadap A. fabae, dan juga antara keeratan genetic dengan tempat asal dari galur-galur tersebut. Analisis AFLP (Amplified Fragment Length Polymorphisms) telah digunakan untuk mengidentifikasi keeratan genetic diantara 20 galur tahan dan 2 galur tidak tahan sebagai control. Tiga kombinasi primer ((PstACA-MseCAG, PstACA-MseCCA dan Ps ACA-MseCGA) menghasilkan polimorpi yang tinggi. Rata-rata keeratan genetic dari semua ke 22 galur adalah 0,34 dengan rentang pasangan dari 0,09 hingga 0,53. Pohon pilogenetik membagi 22 galur menjadi dua grup utama dan beberapa grup terdiri dari dua dan tiga galur. Hasil analisis menunjukkan bahwa keeratan hubungan antara sifat tahan terhadap A. fabae, asal dan populasi sumber tidak dapat disimpulkan dengan nyata.